Yoga versus neuromuscular coordination exercise in improving fall predictor parameters and nerve growth factor levels among adult population: a randomized controlled trial - Wahyuni, Nila; Adiputra, Nyoman; Adiatmika, I Putu Gede; Sundari, Luh Putu Ratna; Indrayani, Agung Wiwiek; Vittala, Govinda (Universitas Udayana, 2024)
Background and purpose: The incidence of fracture-related falls in young adults has been increased and the population with walking disorders has an increased risk of falling. It is very important to improve fall predictor parameters early in adulthood to reduce the risk of falling and injury in the future. This study aims to explore the differences of effectiveness between yoga and neuromuscular coordination exercise in improving several fall predictor parameters and Nerve Growth Factor (NGF) levels. Methods: This study was a randomized controlled trial involving 30 participants who met the inclusion and exclusion criteria. Participants were divided into two groups randomly. Group one was given yoga training intervention and group two was given neuromuscular coordination exercise. Participants` gait speed measurements were carried out using Shuttle Run Test. Participants` agility measurements were carried out using Hexagonal Obstacle Test. Participants` visual and auditory reaction time measurements were carried out using Whole Body Measuring equipment II type TKK – 1264 B. NGF measurement used the ELISA technique. Results: Paired sample Wilcoxon test showed yoga training was effective in improving all fall risk predictor parameters and NGF with p<0.05, but neuromuscular coordination exercise only showed improvement in one fall predictor parameter, namely speed. The unpaired sample Mann Whitney test proved that yoga training was significantly more effective with p<0.05 compared to neuromuscular coordination exercise in improving fall risk parameters, namely agility, visual reaction time, auditory reaction time, but not more effective in improving speed gait and NGF level. Conclusion: The We conclude that yoga training is the most effective exercise in improving fall risk parameters, namely agility, visual and auditory reaction time. Yoga training is a promising intervention in improving various aspects of fall risk.